SOCIO-ECONOMIC CONDITIONS FOR THE APPLICATION OF EVENT TECHNOLOGIES IN PUBLIC POLICY AND MANAGEMENT - Orlova, Olha; Vedenieniev, Vitalii; Orlov, Valentyn; Poliakova, Victoiia; Sadovenko, Maryna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The specificity of public administration is the implementation of social objectives, as it requires the use of effective means of administrative influence, adequate to the needs of the information society. In such circumstances, the concept of event management can be considered as an effective form of interaction between public authorities and the population. The aim of the study is to find ways to increase the effectiveness of public administration bodies through the use of event-marketing and event management technologies. The paper analyses the modern state of the theory and practice of event management in the activities of bodies of public administration. The emphasis is placed on finding of socio-economic determinants that contribute to the need to implement effective models of event-management in activities of government bodies and local self-government. It was determined that the use of event management logically reflects the content of the activities of public authorities in the information society. There is the combination of communicative functions and services for the modern system of public administration.The main prerequisites for the implementation of conceptions of events in the activities of the authorities are the population, the landmark authorities for consumer services as a full participant, relations in the sphere of power, an increase in demand for the combination of entertainment and social elements, the need to increase the population to overcome the political and social absenteeism.